Farmer perspectives on understanding rural household behaviour in agricultural decision-making - Fronda, Jennifer G (Asian Journal of Agriculture and Rural Development, 2023)
This study aims to provide an in-depth understanding of the agricultural decision-making processes undertaken by rural households in Nueva Ecija, Philippines. The goal is to elucidate the significance of individual perceptions, experiences, and risk attitudes in this process and to identify the key elements that influence agricultural decision-making among these households. The research employed a mixed-methods approach to data collection, incorporating both surveys and interviews to gather quantitative and qualitative data. The analysis involved the use of descriptive statistics, chi-square tests, and logistic regression for the quantitative data, while the qualitative data were assessed through thematic analysis. The research’s findings showed that local knowledge and experiences, risk attitudes, and perceptions of climate change among rural households all have a significant impact on agricultural decision-making. Even though risk aversion acted as an obstacle, the prevalent use of local knowledge in decision-making presented itself as an invaluable asset for creating adaptive strategies. Based on these findings, the study recommends the integration of local knowledge into agricultural training programs, the development of efficient risk management strategies, and the promotion of climate-smart agriculture. The results also underscore the need for further exploration of decision-making complexities in future research. These recommendations and findings have substantial implications for designing interventions and policies geared towards sustainable rural development. The study thus contributes significantly to enhancing our understanding of agricultural decision-making, helping to pave the way for sustainability in rural development.